2005
DOI: 10.1191/0269215505cr836oa
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of exercise programmes after lumbar disc surgery: a randomized controlled study

Abstract: It seems that intensive exercise is more effective in reduction of pain and disability, but whether it is cost-effective is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 15 publications
2
62
1
1
Order By: Relevance
“…Yilmaz et al [52], however, found supervised dynamic lumbar stabilisation training to be more beneficial than home-based training, which in turn was more effective than no training. This is a pattern that has also been reported in other studies [4,15].…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Yilmaz et al [52], however, found supervised dynamic lumbar stabilisation training to be more beneficial than home-based training, which in turn was more effective than no training. This is a pattern that has also been reported in other studies [4,15].…”
supporting
confidence: 90%
“…In the Swedish spine register, based on 1,021 disc patients surgically treated during 2003, the corresponding mean levels of leg and back pain at 12-month follow-up were 23 and 26, respectively [46]. The excellent results of the homebased training group were unexpected and contrasting to previous studies, but in those, the control groups had a less active or no exercise programme, and compliance with the prescribed home training was not reported [4,15,52].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Reviewing the data in the literature 3, similar studies analyzed the correlation between spinal surgery and depression. Filiz et al [17] found that physical therapy was most effective in alleviating both the postoperative pain and depression. In patients who had undergone surgery for spinal canal stenosis, treating depression both pre-and post-operatively was vital to the effectiveness of surgery [18].…”
mentioning
confidence: 99%